Non-reproductive system effects of progesterone and its non-selective antagonists mifepristone - А. С. Исаева (Publishing House TRILIST, 2017)
Analysis of the data of progesterone effect on cardiovascular system, bone and muscle function, and nervous system were presented in the paper. Possible effects of progesterone activity inhibition are discussed. Physiological progesterone concentration characterized by its protective effect on cardiovascular system. It was demonstrated in the literature that progesterone significantly influence repolarization process in cardiomyocytes and shorten QT interval. At the same time QT-interval prolongation is a strong marker of the risk of arrhythmia. Also, the hormone decreases apoptosis of cardiomyocytes and increase NO production. Different effects of progesterone on lipid metabolism are described in the paper. Data concerning progesterone influence on central nervous system and its ability to regulate human behavior and influence on the risk of depression and cognitive disorders are given in this review. Progesterone protection effects in patient survived stork are known now. Anabolic effect of the hormone and its ability to increase muscle mass are highly important to maintain women health. Analysis of the data of both branch and clinical studies suggests that the drug interacts with the progesterone receptor and glucocorticoid and less with the androgen receptors (to testosterone). The data showed lack evidence of safety profile for long-term use of mifepristone, the duration of most clinical trials do not exceed 6 months, and more often presented in a dose of 5-10 mg per day. Also, two clinical cases of arrhythmia onset during long-term therapy with mifepristone due to leiomyoma are given to illustrate possible side effects. Without a doubt, scientific data about the safety of long-term use of mifepristone demonstrate the necessity of randomized clinical trials to study possible side effects of the drug on cardiovascular system, bone, muscles and nerves system as well as its metabolic effects.